2018
DOI: 10.3389/fmed.2018.00129
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet-Based Pathogen Inactivation Systems: Untangling the Molecular Targets Activated in Platelets

Abstract: Transfusions of platelets are an important cornerstone of medicine; however, recipients may be subject to risk of adverse events associated with the potential transmission of pathogens, especially bacteria. Pathogen inactivation (PI) technologies based on ultraviolet illumination have been developed in the last decades to mitigate this risk. This review discusses studies of platelet concentrates treated with the current generation of PI technologies to assess their impact on quality, PI capacity, safety, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 154 publications
1
40
0
1
Order By: Relevance
“…Combining Intercept and S/D in the manufacture of pooled HPL can, at least partially, meet these requirements. On the one hand, the Intercept treatment, as applied to PC for transfusion, has been shown to inactivate, moderately to highly effectively, several known or emerging enveloped viruses, but some retroviruses, like human immunodeficiency virus, are known to exert some resistance as they possess repair mechanisms against UV‐based inactivation treatments . In addition, the transmission of the nonenveloped viruses hepatitis E virus (HEV) and parvovirus B19 (PB19V) has been reported in patients receiving Intercept‐treated PCs, and limited inactivation of these two viruses has been reported in experimental studies of Intercept‐PC .…”
Section: Discussionmentioning
confidence: 99%
“…Combining Intercept and S/D in the manufacture of pooled HPL can, at least partially, meet these requirements. On the one hand, the Intercept treatment, as applied to PC for transfusion, has been shown to inactivate, moderately to highly effectively, several known or emerging enveloped viruses, but some retroviruses, like human immunodeficiency virus, are known to exert some resistance as they possess repair mechanisms against UV‐based inactivation treatments . In addition, the transmission of the nonenveloped viruses hepatitis E virus (HEV) and parvovirus B19 (PB19V) has been reported in patients receiving Intercept‐treated PCs, and limited inactivation of these two viruses has been reported in experimental studies of Intercept‐PC .…”
Section: Discussionmentioning
confidence: 99%
“…The INTERCEPT system uses amotosalen (a psoralen) as the photosensitizing agent which, following exposure to ultraviolet (UV)-A light, crosslinks DNA bases. 22 The MIRASOL pathogen-reduced T system uses riboflavin (vitamin B2) and damages nucleic acid bases following UV-A/B light exposure. 22 A third system, Theraflex-UV (Macropharma, Tourcoing, France), uses UV-C light exposure without a photosensitizing agent for pathogen-reduced PLT production and is undergoing a phase III clinical trial in Europe.…”
mentioning
confidence: 99%
“…22 The MIRASOL pathogen-reduced T system uses riboflavin (vitamin B2) and damages nucleic acid bases following UV-A/B light exposure. 22 A third system, Theraflex-UV (Macropharma, Tourcoing, France), uses UV-C light exposure without a photosensitizing agent for pathogen-reduced PLT production and is undergoing a phase III clinical trial in Europe. 22 The clinical efficacy and long-term safety of these products has been a major focus throughout their development.…”
mentioning
confidence: 99%
“…Preclinical studies and clinical trials with PRTs conducted in the preceding 18 years have repeatedly demonstrated changes in both in vitro and in vivo variables . These include changes in metabolic variables in treated PLTs, changes in aggregation, and adhesion function and changes in PLT proteomic and metabolomics measurements . Similar results with plasma products have shown reduced coagulation factor levels after treatment .…”
Section: Session 3 Pathogen Reduction Technologies For Whole Blood Amentioning
confidence: 84%